Kontribusi Pendapatan Tenaga Kerja Wanita terhadap Pendapatan Keluarga (Studi Kasus di KUD Krida Sejahtera Kabupaten Tulang Bawang Provinsi Lampung) - AYUNINGSIH, NI KADEK JIWI; ARTINI, NI WAYAN PUTU; DEWI, NI LUH PRIMA KEMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p20, 2022)
Contribution of Women’s Labor Income to Family Income (Case Study in KUD Krida Sejahtera Tulang Bawang Regency Lampung Province).  Koperasi Unit Desa Krida Sejahtera is located in Bogatama Village, Penawartama Sub-district, Tulang Bawang Regency, Lampung Province, which is a forum for people to develop oil palm plantation businesses. In managing this business, KUD Krida Sejahtera establishes a nucleus-plasma partnership with PT. Sumber Indah Perkasa and absorbs women’s labor as plantation field workers. The purpose of this research is to calculate the contribution of women’s labor income to family income and the motivation that encourages women to work as field worker in the KUD Krida Sejahtera’s oil palm plasma plantation. The results showed that the contribution of the income of the female who work in KUD Krida Sejahtera’s oil palm plasma plantation to the family income is in the medium category with a percentage of 49,71%. Women's labor income is very helpful in improving the standard of living of the family to be better than before. While the motivation that drives women to work as field workers in KUD Krida Sejahtera’s oil palm plasma plantations is that it is necessary to fulfill the three needs stated by Clayton Alderfer, that are the need for existence, relatedness, and growth (ERG). The advice than can be given is that household women are given greater opportunities in the public sphere to develop their potential and can play a productive role such as opening a home industry. For KUD Krida Sejahtera to increase the empowerment of household women by channeling employment opportunities and entrepreneurship development to support women's potential as an effort to help increase women's contribution to the family economy. Then, for further research, it is expected to use other theories besides the ERG theory which can represent the conditions at the research site.